2022
DOI: 10.1002/jmd2.12281
|View full text |Cite
|
Sign up to set email alerts
|

High penetrance, recurrent attacks and thrombus formation in a family with hereditary coproporphyria

Abstract: Hereditary coproporphyria (HCP) is the rarest of the autosomal dominant acute porphyrias with an estimated incidence of 0.02 per 10 million per year. HCP has been considered to be mild in presentation compared with the more common acute intermittent porphyria although there is limited information comparing the subtypes. Penetrance in the acute porphyrias is low with 90% of patients with a mutation never exhibiting symptoms. We present seven members from a family with HCP with a novel mutation in whom penetranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Even though acute neurovisceral attacks are the most dramatic, and potentially life-threatening, clinical manifestations of acute porphyrias, patients affected by this group of diseases do suffer from chronic complications, which may be debilitating and have a considerable impact on their quality of life. In particular, patients with symptomatic AHPs are prone to develop long-term complications of vascular nature, such as arterial hypertension, chronic kidney disease (often termed porphyria-associated kidney disease-PAKD) [ 11 , 13 , 17 , 38 , 39 ], and thrombotic events [ 40 , 41 ]. Therefore, it could be reasonably conjectured a direct involvement of the endothelium, which could be a primary site of organ damage, in the pathogenesis of AHPs.…”
Section: Discussionmentioning
confidence: 99%
“…Even though acute neurovisceral attacks are the most dramatic, and potentially life-threatening, clinical manifestations of acute porphyrias, patients affected by this group of diseases do suffer from chronic complications, which may be debilitating and have a considerable impact on their quality of life. In particular, patients with symptomatic AHPs are prone to develop long-term complications of vascular nature, such as arterial hypertension, chronic kidney disease (often termed porphyria-associated kidney disease-PAKD) [ 11 , 13 , 17 , 38 , 39 ], and thrombotic events [ 40 , 41 ]. Therefore, it could be reasonably conjectured a direct involvement of the endothelium, which could be a primary site of organ damage, in the pathogenesis of AHPs.…”
Section: Discussionmentioning
confidence: 99%
“…40,52 A recent study investigating seven cases of HCP from a single family with a novel mutation found evidence contrasting current literature including a notably high disease penetrance, high rate of severe, recurrent attacks, and a high incidence of venous thromboembolism, a phenomenon not known to be associated with acute porphyria. 53…”
Section: Prevalencementioning
confidence: 99%